ARSITEKTUR TAMAN BERMAIN DALAM FOTOGRAFI EKSPRESI - Paramita, Agra Locita (Seni Media Rekam ISI Surakarta, 2015)
The architecture of the playground in the expression photography is an idea of visual fragment which are visualized become photography art. The characteristics on the deconstruction building consist of irregular lines and unique geometric forms inspire for creating photography art especially in line, form and color elements. The results of the creative processes are photos which are dominant with details or corners of playground building. This creating is expected to give contributions for society through creating new style of architecture photography.Keywords: architecture, playground, photography, and expression